Cover Feature: Mechanistic Study of the Activation and the Electrocatalytic Reduction of Hydrogen Peroxide by Cu‐tmpa in Neutral Aqueous Solution (15/2021). Issue 15 (5th July 2021) - Langerman, Michiel; Hetterscheid, Dennis G. H.
Abstract : The Cover Feature shows an artist impression of the electrochemical reduction of hydrogen peroxide with Cu(tmpa). More information can be found in the Article by M. Langerman and D. G. H. Hetterscheid .